Within-Industry Diversification and Firm Performance in the Presence of Network Externalities: Evidence From the Software Industry - Tanriverdi̇, Hüseyi̇n; Lee, Chi-Hyon (Academy of Management Journal, 2008)
In the presence of network externalities, complementary related diversification strategies in production and consumption can be critical for achieving positive returns to within-industry diversification. This study developed this idea and tested it in a longitudinal study of 884 firms in the software industry. Results indicate that related diversification across operating system platforms and related diversification across software product-markets complement each other and mutually affect each other's marginal returns. Implementing the two strategies in combination improves sales growth and market share. Implementing only market-related diversification reduces sales growth. Implementing only platform-related diversification reduces both sales growth and market share.